A Comparison of Wound Healing Score between Chromic Catgut and Polyglycolic Acid Perineal Suturing at Seven Days Postpartum: A Single Blind Randomized Controlled Trial - Alam, Syaiful (Diponegoro International Medical Journal, 2022)
Background: Perineal Injury is a frequent vaginal delivery complication that can result in dyspareunia, urine and fecal incontinence, granulomas, and discomfort, which can contribute to long-term morbidity. The choice of suture material determines the outcome in perineal injury. This study aims to compare the wound healing scores between chromic catgut and polyglycolic acid perineal suturing at seven days postpartumMethods: Randomized control trial study conducted at 3 hospitals in Indonesia. The patient met our criteria was randomly group into Chromic Catgut as a control and Polyglycolic Acid as a treatment group. After 7 days of perineal suturing, the wound healing was assessed with REEDA (redness, edema, ecchymosis, discharge, approximation) score by the chosen operator.Results:  No significant difference in each indicator of the REEDA score (p>0.05). Most of the indicators are each dominated by a score of 0. The maximum score for redness is 2, the score for edema is 1, the score for ecchymosis and discharge is 0, the approximation score is 1, and the total score is 4. On hematological examination, polyglycolic acid showed lower hemoglobin levels and higher leukocyte levels compared to chromic catgut (p=0.025 and 0.005, respectively).Conclusion: There was no difference in wound healing score between Chromic Catgut and Polyglycolic Acid Perineal Suturing at Seven Days Postpartum.